Manufacturing method of eyeglass lenses

The spin coating method addresses the issues of liquid pools and uneven anti-fog layer distribution in the dipping method by forming uniform, water-absorbing anti-fog layers on both sides of eyeglass lenses, enhancing anti-fog performance and manufacturing efficiency.

JP7653510B2Active Publication Date: 2025-03-28HOYA LENS THAILAND LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023511715
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-31
Publication Date
2025-03-28
Estimated Expiration
2042-03-31

AI Technical Summary

Technical Problem

The dipping method for forming anti-fog layers on eyeglass lenses often results in liquid pools and droplets, leading to uneven distribution and product defects, especially when forming thick layers or different performance layers on both sides of the lens.

Method used

A spin coating method is used to apply a coating liquid containing a water-absorbing anti-fog layer composition to at least one surface of the eyeglass lens substrate, allowing for the formation of uniform anti-fog layers with controlled thickness on both sides of the lens.

Benefits of technology

The spin coating method effectively prevents liquid ponds and allows for the formation of the same or different anti-fog layers on both sides of the lens, improving anti-fog performance and enabling efficient manufacturing of eyeglass lenses with desired functions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653510000014
    Figure 0007653510000014
  • Figure 0007653510000015
    Figure 0007653510000015
  • Figure 0007653510000016
    Figure 0007653510000016
Patent Text Reader

Abstract

A method for producing a spectacle lens according to one embodiment of the present disclosure includes coating, by a spin coating method, at least one surface of a base material with a coating liquid that contains a water-absorbing antifogging layer composition, to form a water-absorbing antifogging layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for manufacturing eyeglass lenses. [Background technology]

[0002] As a technique for preventing lenses such as glasses from fogging, it is common to form an anti-fogging layer by applying a surfactant to the surface. In this case, the effect lasts for a very short time, and the effect cannot be maintained unless the surfactant is applied again in a few days. In addition, when dirt on an optical article is wiped off with water or the like, the anti-fogging layer of the surfactant disappears along with the dirt, and the anti-fogging effect is lost. In addition, the anti-fogging layer formed by applying a surfactant to the surface is insufficient in preventing "fogging" in a high humidity environment, and there is room for improvement. Therefore, recently, a technique for preventing "fogging" by applying a water-absorbing substance to the article substrate instead of a surfactant and forming an anti-fogging layer with water-absorbing properties has been considered (for example, Patent Documents 1 and 2).

[0003] Here, known methods for forming various functional layers on spectacle lenses include, for example, air spraying, airless spraying, electrostatic coating, roll coater, flow coater, spin coating, dipping, etc. On the other hand, the formation of an anti-fogging layer is mainly carried out by the dipping method, in which the lens is immersed in an immersion liquid containing an anti-fogging layer composition, mainly from the viewpoint of productivity. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2000-75104 A [Patent Document 2] International Publication No. 2013 / 005710 Summary of the Invention [Problem to be solved by the invention]

[0005] However, when a thick anti-fogging layer is formed to provide various functions, the dip method tends to cause liquid puddles around the edge of the eyeglass lens. Even when the viscosity of the coating liquid is high, the dip method tends to cause liquid puddles. If liquid puddles occur, the anti-fogging layer may not be distributed uniformly, which may result in a defective product. In addition, it may be required to form anti-fogging layers with different performance or thickness on one side and the other side of the eyeglass lens. In this way, it may be difficult to deal with the situation when the anti-fogging layer is formed by the dip method. In response to the above-mentioned problems, an object of one embodiment of the present disclosure is to provide a method for manufacturing eyeglass lenses that is capable of forming the same or different anti-fogging layers on both sides of a substrate with almost no liquid pooling. [Means for solving the problem]

[0006] The embodiments of the present disclosure relate to the following [1] to

[13] . [1] A method for producing a spectacle lens, comprising applying a coating liquid containing a water-absorbent anti-fogging layer composition to at least one surface of a substrate by spin coating to form a water-absorbent anti-fogging layer. [2] The method for producing a spectacle lens according to [1] above, wherein the water-absorbing anti-fogging layer composition contains a structural unit derived from acrylamide. [3] The method for manufacturing a spectacle lens according to [1] or [2] above, further comprising forming an anti-fogging layer on the other surface of the substrate by a spin coating method. [4] The method for manufacturing a spectacle lens according to [3] above, wherein the thickness of the water-absorptive anti-fogging layer on the one surface and the thickness of the anti-fogging layer on the other surface are the same or different. [5] The method for manufacturing a spectacle lens according to [3] or [4] above, wherein the anti-fogging layer on the other surface is a water-absorbent anti-fogging layer or a hydrophilic anti-fogging layer. [6] The method for producing a spectacle lens according to any one of [1] to [5] above, further comprising applying a coating liquid containing the water-absorbing anti-fogging layer composition to the other surface of the substrate by spin coating to form a water-absorbing anti-fogging layer. [7] The method for producing a spectacle lens according to any one of the above [1] to [6], wherein the water-absorbing antifogging layer is formed directly on at least one surface of the substrate. [8] A method for producing a spectacle lens according to any one of the above [1] to [5], comprising carrying out the following steps 1 to 3 in this order: Step 1: A coating liquid containing the water-absorbing anti-fogging layer composition is applied to one surface of the substrate by spin coating to form a water-absorbing anti-fogging layer. Step 2: An anti-reflection layer is formed on the other surface of the substrate. Step 3: On the other side of the substrate having the antireflection layer obtained in step 2, a hydrophilic antifogging layer is formed. [9] The method for producing a spectacle lens according to [8] above, further comprising forming a hard coat layer on at least the other surface of the substrate before carrying out step 1 or step 2.

[10] The method for producing a spectacle lens according to any one of the above [1] to [9], wherein one surface of the substrate is concave and the other surface of the substrate is convex.

[11] The method for producing a spectacle lens according to any one of the above [1] to

[10] , wherein the water-absorbing anti-fogging layer on at least one of the surfaces is the outermost layer.

[12] The method for producing a spectacle lens according to any one of the above [1] to

[11] , wherein the water-absorbing anti-fogging layer on at least one of the surfaces is a single layer.

[13] The method for producing a spectacle lens according to any one of the above [1] to

[12] , wherein the water-absorbing anti-fogging layer composition comprises the following components (A) to (C): Component (A): A (meth)acrylic resin (A) having a structural unit derived from a monomer (a-1) represented by the following general formula (1), a structural unit derived from a monomer (a-2) represented by the following general formula (2), a structural unit derived from a hydroxyalkyl (meth)acrylate (a-3), and a structural unit derived from a monomer (a-4) represented by the following general formula (3): Component (B): Polyol compound (B) Component (C): Polyfunctional isocyanate compound (C) [ka] [In general formula (1), R1 is a hydrogen atom or a methyl group, R2 and R3 are each independently a hydrogen atom or a linear or branched alkyl group having 1 to 3 carbon atoms, and R2 and R3 may be the same or different.] [ka] [In general formula (2), R4 is a hydrogen atom or a methyl group, and m is an integer of 1 to 5.] [ka] [In general formula (3), R5 is a hydrogen atom or a methyl group, R6 is a divalent organic group, and n is an integer of 0 or 1 or more.] Effect of the Invention

[0007] According to one embodiment of the present disclosure, it is possible to provide a method for manufacturing a spectacle lens that is capable of forming the same or different anti-fogging layers on both sides of a substrate with almost no liquid pooling. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic cross-sectional view of a spectacle lens manufactured according to one embodiment of the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view of a spectacle lens manufactured according to one embodiment of the present disclosure. [Diagram 3] FIG. 2 is a schematic cross-sectional view of a reference eyeglass lens. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments and examples of the present disclosure will be described. The same or corresponding parts are given the same reference symbols, and their descriptions may not be repeated. In the embodiments and examples described below, when numbers, amounts, etc. are mentioned, the scope of the present disclosure is not necessarily limited to the numbers, amounts, etc., unless otherwise specified. In the following embodiments, each component is not necessarily essential for the embodiments and examples of the present disclosure, unless otherwise specified.

[0010] In the description of groups (atomic groups) in this specification, when a notation does not specify whether the group is substituted or unsubstituted, the notation includes both groups having no substituents and groups having a substituent. For example, an "alkyl group" includes an alkyl group having no substituents (an unsubstituted alkyl group) and an alkyl group having a substituent (a substituted alkyl group). In this specification, the term "(meth)acrylic" refers to a concept that includes both acrylic and methacrylic. The same applies to similar terms such as "(meth)acrylate." In this specification, a structural unit derived from monomer (a-1) may be referred to as a "structural unit (a-1)," a structural unit derived from monomer (a-2) as a "structural unit (a-2)," a structural unit derived from monomer (a-3) as a "structural unit (a-3)," and a structural unit derived from monomer (a-4) as a "structural unit (a-4)."

[0011] The "solid content" of a composition means the amount of components other than the solvent. The "number of carbon atoms" of a group having a substituent refers to the number of carbon atoms excluding the above-mentioned substituent.

[0012] The method for manufacturing a spectacle lens according to this embodiment involves applying a coating liquid containing a water-absorbent anti-fogging layer composition to at least one surface of a substrate by spin coating to form a water-absorbent anti-fogging layer. In the manufacturing method of the spectacle lens according to the present embodiment, a coating liquid containing a water-absorbent anti-fogging layer composition is applied by spin coating to form a water-absorbent anti-fogging layer, so that the same or different water-absorbent anti-fogging layers can be formed on both sides of the substrate with almost no liquid pooling. In addition, in the manufacturing method of the spectacle lens according to the present embodiment, a coating liquid containing a water-absorbent anti-fogging layer composition is applied by spin coating, so that even if a relatively thick water-absorbent anti-fogging layer is formed, or even if the coating liquid containing a water-absorbent anti-fogging layer composition has a high viscosity, it is expected that almost no liquid pooling will occur. In addition, the same or different anti-fogging layers or the same or different layer configurations can be formed on both sides of the substrate. Furthermore, it is required that the specifications of eyeglass lenses be changed for each wearer. For example, the curvature of eyeglass lenses varies depending on the lens power. Also, the spin coating method often requires less coating liquid than the dip coating method. The eyeglass lens manufacturing method according to the present embodiment can impart anti-fogging performance individually according to the lens curvature, and is therefore expected to be able to efficiently handle small-volume production. Therefore, according to the method for manufacturing a spectacle lens according to this embodiment, the anti-fogging performance of the water-absorbent anti-fogging layer is improved, and it is expected that spectacle lenses to which the desired functions are favorably imparted can be efficiently manufactured.

[0013] [Base material] In this embodiment, the substrate is a lens substrate that constitutes a spectacle lens. The substrate may be made of resins made from various kinds of raw materials. Examples of resins that form the substrate include polycarbonate resins, urethane urea resins, (thio)urethane resins, polysulfide resins, polyamide resins, polyester resins, acrylic allyl resins, and allyl carbonate resins. The (thio)urethane resin means at least one selected from thiourethane resins and urethane resins. Among these, (thio)urethane resins and polysulfide resins are preferred.

[0014] Furthermore, the substrate used in the spectacle lens of this embodiment preferably has a refractive index of 1.50 or more, and is more preferably a plastic lens substrate having a refractive index of 1.60 or more. Preferred commercially available plastic lens substrates include an allyl carbonate-based plastic lens "HILUX1.50" (manufactured by HOYA Corporation, refractive index 1.50), a thiourethane-based plastic lens "MERIA" (manufactured by HOYA Corporation, refractive index 1.60), a thiourethane-based plastic lens "EYAS" (manufactured by HOYA Corporation, refractive index 1.60), a thiourethane-based plastic lens "EYNOA" (manufactured by HOYA Corporation, refractive index 1.67), a polysulfide-based plastic lens "EYRY" (manufactured by HOYA Corporation, refractive index 1.70), and a polysulfide-based plastic lens "EYVIA" (manufactured by HOYA Corporation, refractive index 1.74).

[0015] The thickness and diameter of the substrate are not particularly limited, but the thickness is usually about 1 to 30 mm, and the diameter is usually about 50 to 100 mm. The substrate may be either a finished lens or a semi-finished lens. The surface shape of the substrate is not particularly limited, and may be any of a flat surface, a convex surface, a concave surface, and the like. In this embodiment, the eyeglass lens may be any of a single-focus lens, a multifocal lens, a progressive-power lens, etc. In the case of a progressive-power lens, the near area (near area) and the progressive area (intermediate area) are usually included in the lower area, and the distance area (distance area) is included in the upper area.

[0016] [Spin ​​coating method] In this embodiment, a coating liquid containing a water-absorbing anti-fogging layer composition is applied to at least one surface of a substrate by spin coating to form a water-absorbing anti-fogging layer. The spin coating method for forming the water-absorbing anti-fogging layer will be described below. Spin coating can be performed, for example, by placing the substrate in a spin coater. The rotation can be, for example, about the geometric center of the substrate. The coating liquid may be supplied, for example, to the geometric center of the rotating substrate. Alternatively, the coating liquid may be applied to the rotating substrate by moving the coating liquid horizontally on a straight line connecting the geometric center and the peripheral edge of the substrate so that the coating liquid supply point describes a spiral trajectory on the substrate. The amount of the coating solution to be supplied can be appropriately determined depending on the desired thickness. The amount of the coating solution to be supplied is usually about 1 to 10 ml, and preferably 2 to 5 ml.

[0017] In the first stage, when the supply of the coating liquid starts (when the liquid is discharged), the rotation is performed at a low rotation speed so that the coating liquid to be supplied is not repelled by the substrate. The rotation speed in the first stage is preferably 200 to 600 rpm, more preferably 250 to 500 rpm, and further preferably 285 to 450 rpm. The retention time at the above rotation speed can usually be about 1 to 10 seconds, preferably 2 to 6 seconds.

[0018] Next, in the second stage, after the start of the supply of the coating liquid, the rotation speed is usually increased to 600 rpm or more to spread the coating liquid on the coating surface. The rotation speed in the second stage is preferably 700 to 1500 rpm, more preferably 800 to 1300 rpm, and even more preferably 900 to 1200 rpm. If it is within the above numerical range, the coating liquid can be well shaken off. The retention time at the above rotation speed can usually be about 1 to 10 seconds, preferably 1 to 6 seconds.

[0019] After coating, it is preferable to carry out pre-baking usually at about 20 to 160°C, preferably 70 to 120°C, more preferably 75 to 110°C, and further preferably 80 to 100°C. The time for the above pre-baking can usually be about 5 to 100 minutes, preferably 10 to 60 minutes, and more preferably 15 to 40 minutes. After the above-mentioned pre-firing, the product is usually subjected to main firing at a temperature equal to or higher than the temperature during the pre-firing, preferably 70 to 160°C, more preferably 85 to 140°C, and further preferably 100 to 130°C. The time for the main baking can usually be about 30 to 150 minutes, preferably 60 to 140 minutes, and more preferably 90 to 130 minutes. The water-absorbing anti-fogging layer is obtained by drying and curing the coating by the main baking and then cooling it at room temperature. The temperature and time for drying and curing may be appropriately adjusted in consideration of the type of solvent, the heat resistance of the substrate, and the like.

[0020] In addition, in this embodiment, from the viewpoint of further improving the anti-fogging performance, an anti-fogging layer can be formed on the other side of the substrate by spin coating. The anti-fogging layer formed on the other side is not particularly limited as long as it does not impair the effects of the present disclosure. The anti-fogging layer formed on the other side may be, for example, a water-absorbent anti-fogging layer or a hydrophilic anti-fogging layer. In this case, the water-absorbent anti-fogging layer formed on the other side may have the same composition as the water-absorbent anti-fogging layer formed on one side, or may have a different composition.

[0021] In this embodiment, the thickness of the water-absorbing anti-fogging layer on one side and the thickness of the anti-fogging layer on the other side can be formed to be the same or different. In this specification, the term "same" means not only that the thicknesses of the two layers are completely the same, but also that there is a difference in the thicknesses to a degree that is recognized as substantially the same in the technical field. Specifically, the thickness difference ratio shown in the following formula is usually about 10% or less, and preferably 5% or less. Thickness difference ratio (%) = [(ab) / a] × 100 In the above formula, a and b are the layer thicknesses, and a≧b. In addition, when the surface shape of the substrate has a convex surface and a concave surface, the water-absorbent anti-fogging layer can be formed on either the convex surface or the concave surface. For example, when one surface of the substrate is concave and the other surface of the substrate is convex, the water-absorbent anti-fogging layer is formed at least on the concave surface side. In this manner, in this embodiment, the same or different anti-fogging layers can be formed on both sides of the substrate depending on the desired specifications of the eyeglass lens.

[0022] [Water-absorbing anti-fog layer] The water-absorbing anti-fogging layer can be formed by curing a coating liquid containing a water-absorbing anti-fogging layer composition. The water-absorbing anti-fogging layer is a layer formed on at least one side of a substrate, and is a layer having water absorption. Here, "water absorption" means that the material exhibits the property of absorbing moisture. After storing the transparent substrate on which the water-absorbing anti-fogging layer is formed at room temperature, the transparent substrate with the anti-fogging layer is placed at a position 35 mm away from the surface of 40°C hot water and exposed to steam from the hot water for 15 seconds. This means that there is no diffuse reflection on the surface of the water-absorbing anti-fogging layer due to fine water droplets, and there is no distortion due to condensation in the image seen through the transparent substrate with the water-absorbing anti-fogging layer after contact with the steam.

[0023] The water-absorbent anti-fogging layer formed on at least one surface of the substrate is preferably provided as the outermost layer of the spectacle lens from the viewpoint of fully exerting anti-fogging performance. By using a water-absorbent anti-fogging layer composition containing the components (A) to (C) described below, the water-absorbent anti-fogging layer can exhibit high durability even if it is located as the outermost layer of the spectacle lens. The water-absorbing anti-fogging layer may be formed on only one surface of the substrate, or on both surfaces. For example, a coating solution containing a water-absorbing anti-fogging layer composition may be applied to the other surface of the substrate by spin coating to form a water-absorbing anti-fogging layer.

[0024] The water-absorptive anti-fogging layer may be formed as a single layer or as multiple layers on at least one surface of the substrate. From the viewpoint of productivity, the water-absorptive anti-fogging layer is preferably formed as a single layer. From the viewpoint of anti-fogging durability, the water-absorbing anti-fogging layer may be formed directly on at least one surface of the substrate.

[0025] The thickness of the water-absorbent anti-fogging layer is about 0.05 to 100 μm, but is not particularly limited. On the other hand, from the viewpoint of improving anti-fogging performance and scratch resistance, the thickness of the water-absorbent anti-fogging layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, even more preferably 0.8 μm or more, still more preferably 1 μm or more, and even more preferably 5 μm or more. In addition, from the viewpoint of improving anti-fogging performance and forming a uniform layer, the thickness of the water-absorbent anti-fogging layer is preferably 60 μm or less, more preferably 50 μm or less, even more preferably 40 μm or less, still more preferably 30 μm or less, and even more preferably 20 μm or less.

[0026] When a thick anti-fogging layer is formed by the dipping method, liquid puddles are likely to occur, which may cause defects. However, in the present embodiment, even if the water-absorbent anti-fogging layer is thick, the water-absorbent anti-fogging layer can be formed without causing liquid puddles. Therefore, the thicker the water-absorbent anti-fogging layer is, the more pronounced the effect of the present disclosure tends to be. Furthermore, according to the method for manufacturing a spectacle lens according to this embodiment, when forming a water-absorbent anti-fogging layer on one side and the other side of a substrate, the water-absorbent anti-fogging layer can be formed on each side at a time, so that the thickness of the water-absorbent anti-fogging layer on one side and the thickness of the water-absorbent anti-fogging layer on the other side can be formed to be the same or different.

[0027] [Coating solution containing water-absorbing anti-fogging layer composition] <Water-absorbing anti-fog layer composition> The water-absorbing anti-fogging layer composition (hereinafter, simply referred to as "anti-fogging layer composition") preferably contains a structural unit derived from acrylamide. When the anti-fogging layer composition contains an amide group derived from acrylamide, the water-absorbing anti-fogging layer has high hydrophilicity, which improves the water absorption performance and the anti-fogging performance.

[0028] From the viewpoint of obtaining an anti-fogging layer having excellent anti-fogging performance, the anti-fogging layer composition preferably contains the following components (A) to (C). Component (A): A (meth)acrylic resin (A) having a structural unit derived from a monomer (a-1) represented by the following general formula (1), a structural unit derived from a monomer (a-2) represented by the following general formula (2), a structural unit derived from a hydroxyalkyl (meth)acrylate (a-3), and a structural unit derived from a monomer (a-4) represented by the following general formula (3): Component (B): Polyol compound (B) Component (C): Polyfunctional isocyanate compound (C)

[0029] [ka] [In general formula (1), R1 is a hydrogen atom or a methyl group, and R2 and R3 each independently is a hydrogen atom or a linear or branched alkyl group having 1 to 3 carbon atoms.] [ka] [In general formula (2), R4 is a hydrogen atom or a methyl group, and m is an integer of 1 to 5.] [ka] [In general formula (3), R5 is a hydrogen atom or a methyl group, R6 is a divalent organic group, and n is an integer of 0 or 1 or more.]

[0030] The structural unit (a-1) contained in the component (A) (also called a (meth)acrylic resin) has an amide group, is highly hydrophilic, and easily holds moisture. For this reason, it is believed that moisture adhering to the surface of the water-absorbent anti-fogging layer obtained by curing the anti-fogging layer composition is easily absorbed into the cured interior. In addition, it is believed that by blending the polyol compound (B), it is possible to maintain the crosslink density required for a water-absorbent anti-fogging layer while creating gaps that allow sufficient absorption of moisture. It is believed that these reasons impart water-absorbent anti-fogging performance.

[0031] In addition, the structural unit (a-2) contained in the resin (A) is a structural unit having a polycaprolactone structure, and its flexible chemical skeleton contributes to improving the flexibility and elasticity of the water-absorbent anti-fogging layer. In addition, the structural unit (a-3), which is more rigid than the structural unit (a-2), ensures a balance between flexibility and elasticity in the water-absorbent anti-fogging layer. On the other hand, the polydimethylsiloxane chain of the structural unit (a-4) contributes to improving the slipperiness of the water-absorbent anti-fogging layer. Therefore, when an external force is applied to the water-absorbent anti-fogging layer, the flexibility and elasticity of the water-absorbent anti-fogging layer absorbs the external force, while the slipperiness releases the external force to the outside of the water-absorbent anti-fogging layer, and the above two effects are expressed synergistically. As a result, it is considered that the water-absorbent anti-fogging layer is less susceptible to scratches.

[0032] The anti-fog layer composition preferably contains, relative to 100 mass% of all structural units constituting component (A), a proportion of structural units derived from monomer (a-1) of 20 mass% or more and 65 mass% or less, a proportion of structural units derived from monomer (a-2) of 10 mass% or more and 40 mass% or less, and a proportion of structural units derived from monomer (a-4) of 1 mass% or more and 10 mass% or less, and has a ratio (NCO) / (OH) of the number of isocyanate groups contained in component (C) to the total amount (OH) obtained by adding up the number of hydroxyl groups contained in component (A) and the number of hydroxyl groups contained in component (B), of 0.15 or more and 0.55 or less. It is believed that by formulating the anti-fogging layer composition in this way, the equivalent ratio (NCO / OH) can be set to a specific range less than 1 while maintaining a balance (quantitative ratio) between the hydroxyl-containing structural unit (a-2) and the structural unit (a-3) in component (A), and the hardness of the water-absorbing anti-fogging layer can be increased to a degree that improves frictional resistance. In addition, it is believed that the crosslink density of the water-absorbing anti-fogging layer is increased and the solvent resistance of the water-absorbing anti-fogging layer is improved while maintaining a structural balance between the hydroxyl-containing structural unit (a-2) and the structural unit (a-3) in component (A), and the equivalent ratio (NCO / OH) can be set to a specific range less than 1.

[0033] The components contained in the water-absorbing anti-fogging layer composition will be described below. [Component (A): (meth)acrylic resin] The water-absorbing anti-fogging layer composition preferably contains a (meth)acrylic resin as component (A), that is, a (meth)acrylic resin having a structural unit derived from monomer (a-1) represented by the above general formula (1), a structural unit derived from monomer (a-2) represented by the above general formula (2), a structural unit derived from hydroxyalkyl (meth)acrylate (a-3), and a structural unit derived from monomer (a-4) represented by the above general formula (3).

[0034] As mentioned above, it is believed that the structural unit (a-1) is primarily involved in absorbing water (moisture). The (meth)acrylic resin can typically be obtained by polymerizing the monomers (a-1), (a-2), (a-3) and (a-4). The polymerization method will be described later in detail.

[0035] In this embodiment, 100% of the structural units constituting the (meth)acrylic resin do not have to be structural units derived from (meth)acrylic monomers. That is, the (meth)acrylic resin may contain some (but not all) structural units derived from monomers that are not (meth)acrylic. In order to fully obtain the effect derived from the (meth)acrylic structure, it is preferable that 50% by mass or more of the total structural units of the (meth)acrylic resin are structural units derived from (meth)acrylic monomers. More preferably, 80% by mass or more of the total structural units of the (meth)acrylic resin are structural units derived from (meth)acrylic monomers. Even more preferably, all (100%) of the structural units of the (meth)acrylic resin are structural units derived from (meth)acrylic monomers.

[0036] The monomer (a-1) is not particularly limited as long as it has the structure of the above-mentioned general formula (1).Specific examples include (meth)acrylamide, N-methylacrylamide, N,N-dimethyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, Nn-propyl(meth)acrylamide, and N-isopropyl(meth)acrylamide.

[0037] The monomer (a-1) may be at least one kind, or may be a combination of two or more kinds. For example, the (meth)acrylic resin may be obtained by carrying out a polymerization reaction using two or more kinds of the monomers listed above.

[0038] From the viewpoint of improving anti-fogging performance, it is particularly preferable that the monomer (a-1) contains N,N-dimethyl(meth)acrylamide or N,N-diethyl(meth)acrylamide.

[0039] In this embodiment, the content of the structural units derived from the monomer (a-1) in the (meth)acrylic resin is preferably 20 to 65% by mass, more preferably 35 to 60% by mass, and even more preferably 40 to 55% by mass, based on the total structural units of the (meth)acrylic resin. If the structural units derived from the monomer (a-1) are 20% by mass or more, it becomes easy to form a water-absorbing anti-fogging layer that exhibits anti-fogging performance suitable for practical use, and if they are 65% by mass or less, it is possible to avoid a relative decrease in the ratio of structural units derived from other monomers, making it easier to maintain a balance in the composition as a whole.

[0040] The monomer (a-2) is not particularly limited as long as it has the structure of the above-mentioned general formula (2). In this embodiment, the (meth)acrylic resin contains structural units derived from the monomer (a-2) in an amount of preferably 10 to 40 mass%, more preferably 20 to 38 mass%, and even more preferably 25 to 35 mass%, based on all structural units of the (meth)acrylic resin.

[0041] When the content of the structural units derived from monomer (a-2) is 10% by mass or more, the flexibility of the water-absorbing anti-fogging layer is easily ensured, and when it is 40% by mass or less, the elasticity of the water-absorbing anti-fogging layer is easily ensured. The (meth)acrylic resin may contain a plurality of types of repeating units derived from the monomer (a-2).

[0042] The monomer (a-3) is a hydroxyalkyl (meth)acrylate. Specific examples thereof include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate. In the present embodiment, hydroxyethyl (meth)acrylate is preferred among these. In this embodiment, the content of the structural units derived from the monomer (a-3) in the (meth)acrylic resin is preferably 1 to 30 mass %, more preferably 2 to 20 mass %, and even more preferably 3 to 15 mass %, based on the total structural units of the (meth)acrylic resin.

[0043] The monomer (a-3), like the monomer (a-2), has a hydroxyl group and undergoes a crosslinking reaction with a polyfunctional isocyanate compound described below to form a water-absorbing antifogging layer. In this embodiment, instead of causing a crosslinking reaction using only monomer (a-2) to form a water-absorbent anti-fogging layer, a water-absorbent anti-fogging layer having various physical properties can be obtained by causing a crosslinking reaction between monomer (a-3) and a polyfunctional isocyanate compound.

[0044] As described above, the (meth)acrylic resin contains structural units derived from the monomer (a-2) and the monomer (a-3), and therefore has hydroxyl groups as a whole, i.e., is a resin having a hydroxyl value. Therefore, it can react with the polyol compound described below and the polyfunctional isocyanate compound described below to form a crosslinked structure.

[0045] The hydroxyl value of the (meth)acrylic resin is preferably 40 to 150 mgKOH / g, more preferably 70 to 140 mgKOH / g, and even more preferably 90 to 130 mgKOH / g. By setting the value within the above range, the resin reacts with the polyol compound (described later) and the polyfunctional isocyanate compound (described later), and the crosslinked structure is easily controlled appropriately. Therefore, it is possible to harden the water-absorbent anti-fogging layer while maintaining its flexibility and elasticity. Therefore, it is easy to achieve a higher level of compatibility between the scratch resistance, reduced friction resistance, and solvent resistance of the water-absorbent anti-fogging layer. The hydroxyl value means the number of milligrams of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of a sample is acetylated.

[0046] The monomer (a-4) is not particularly limited as long as it has the structure of the above-mentioned general formula (3).

[0047] The (meth)acrylic resin may contain a plurality of repeating units derived from the monomer (a-4). For example, the (meth)acrylic resin may be obtained by carrying out a polymerization reaction using two or more of the monomers listed above. In this embodiment, the content of the structural units derived from the monomer (a-4) in the (meth)acrylic resin is preferably 1 to 10 mass %, more preferably 2 to 8 mass %, and even more preferably 3 to 7 mass %, based on the total structural units of the (meth)acrylic resin.

[0048] When the content of the structural unit derived from the monomer (a-4) is 1% by mass or more, a water-absorbing anti-fogging layer having satisfactory scratch resistance is easily obtained, and when the content is 10% by mass or less, a homogeneous (meth)acrylic resin is easily synthesized.

[0049] The (meth)acrylic resin may or may not contain any structural unit (structural unit (a-5)) other than the structural unit (a-1), the structural unit (a-2), the structural unit (a-3), and the structural unit (a-4). Examples of the structural unit (a-5) include structural units derived from the monomers shown below. By including such a structural unit in the (meth)acrylic resin, it is possible to adjust and optimize the glass transition temperature of the (meth)acrylic resin and the physical properties of the water-absorbing anti-fogging layer (hardness, softness, etc. of the water-absorbing anti-fogging layer).

[0050] Examples of the structural unit (a-5) include structural units derived from monomers having the general formula CH2=CR-COO-R', where R is a hydrogen atom or a methyl group, and R' is an alkyl group, a monocyclic or polycyclic cycloalkyl group, an aryl group, or an aralkyl group. Specific examples of this monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-stearyl (meth)acrylate, phenyl (meth)acrylate, and benzyl (meth)acrylate. Among these, those in which R' is an alkyl group having 1 to 8 carbon atoms are preferred, those in which R' is an alkyl group having 1 to 6 carbon atoms are more preferred, and those in which R' is an alkyl group having 1 to 4 carbon atoms are even more preferred.

[0051] The (meth)acrylic resin may contain a plurality of repeating units corresponding to the structural unit (a-5). For example, the (meth)acrylic resin may be obtained by carrying out a polymerization reaction using two or more of the monomers listed above as specific examples. When the (meth)acrylic resin contains the structural unit (a-5), the content thereof is preferably 1 to 40 mass%, more preferably 3 to 30 mass%, and even more preferably 5 to 20 mass%, based on all structural units of the (meth)acrylic resin.

[0052] The mass average molecular weight (Mw) of the (meth)acrylic resin is not particularly limited, but is preferably 10,000 to 100,000, more preferably 20,000 to 70,000, and even more preferably 30,000 to 60,000. If the mass average molecular weight is 10,000 or more, the desired anti-fogging performance is easily obtained, and if it is 100,000 or less, there is a tendency for excellent coating suitability when coating a spectacle lens. The mass average molecular weight can be determined by gel permeation chromatography (GPC) using polystyrene as a standard substance.

[0053] The glass transition temperature of the (meth)acrylic resin is not particularly limited, but is preferably 20 to 120°C, more preferably 30 to 110°C, and further preferably 35 to 100°C. The glass transition temperature of the (meth)acrylic resin can be determined by various methods, but for example, it can be determined based on the following Fox formula. 1 / Tg=(W1 / Tg1)+(W2 / Tg2)+(W3 / Tg3)+···+(W n / Tg n ) In the formula, Tg is the glass transition temperature of the (meth)acrylic resin (K), W1, W2, W3...W n are the mass fractions of the respective monomers, Tg1, Tg2, Tg3, Tg n indicates the glass transition temperature (K) of a homopolymer composed of monomers corresponding to the mass fraction of each monomer.

[0054] In this specification, the glass transition temperature of the (meth)acrylic resin (not the glass transition temperature of the water-absorbing anti-fogging layer, but the glass transition temperature of the (meth)acrylic resin alone) means the glass transition temperature calculated based on the above formula. Note that, for monomers whose glass transition temperatures are unknown, such as special monomers and polyfunctional monomers, the glass transition temperature is calculated using only monomers whose glass transition temperatures are known.

[0055] The (meth)acrylic resin can typically be obtained by a polymerization reaction. The polymerization reaction may be any of various methods such as radical polymerization, cationic polymerization, and anionic polymerization, among which radical polymerization is preferred. The polymerization may be any of solution polymerization, suspension polymerization, and emulsion polymerization. Among these, solution polymerization is preferred from the viewpoint of precise control of polymerization.

[0056] As the polymerization initiator for radical polymerization, known initiators can be used. For example, azo initiators such as azobisisobutyronitrile, 2,2-azobis(2-methylbutyronitrile), 2,2-azobis(2-methylpropionitrile), and 2,2-azobis(2,4-dimethylvaleronitrile), peroxide initiators such as benzoyl peroxide, t-butylperoxyoctanoate, diisobutyl peroxide, di(2-ethylhexyl)peroxypivalate, decanoyl peroxide, t-butylperoxy-2-ethylhexanoate, and t-butylperoxybenzoate, and redox initiators combining an oxidizing agent and a reducing agent such as hydrogen peroxide and an iron(II) salt, persulfate and sodium hydrogen sulfite, etc. may be used alone or in combination of two or more. The amount of the polymerization initiator to be added is not particularly limited, but is preferably 0.001 to 10 parts by mass relative to 100 parts by mass of the entire mixed solution of the monomers to be polymerized.

[0057] In addition, in the polymerization reaction, a known chain transfer agent, polymerization inhibitor, molecular weight regulator, etc. may be used as appropriate. Furthermore, the polymerization reaction may be carried out in one stage or in two or more stages. The temperature of the polymerization reaction is not particularly limited, but is typically within the range of 50°C to 200°C, preferably 80°C to 150°C.

[0058] [Component (B): Polyol compound] The water-absorbing anti-fogging layer composition preferably contains a polyol compound. By containing the polyol compound, it is possible to form a water-absorbing anti-fogging layer having better anti-fogging durability by reacting with a polyfunctional isocyanate compound described later together with a (meth)acrylic resin. The number of hydroxyl groups in one molecule of the polyol compound is 2 or more, preferably 2 to 6, and more preferably 2 to 4.

[0059] The polyol compound preferably contains at least one polyol compound selected from the group consisting of polycaprolactone polyol, polycarbonate polyol, and polyether polyol. These chemical structures have moderate flexibility and elasticity. Therefore, the flexibility and elasticity of the water-absorbing anti-fogging layer can be further improved.

[0060] The polycaprolactone polyol can be used without any particular limitation so long as it is a compound having a caprolactone ring-opening structure and two or more hydroxyl groups in one molecule.

[0061] The polycarbonate polyol can be used without any particular limitation as long as it is a compound having a carbonate group represented by -O-(C=O)-O- and two or more hydroxyl groups in one molecule. The polycarbonate polyol can be obtained by reacting one or more polyol raw materials (polyhydric alcohols) with a carbonate ester or phosgene. The polyol raw material is not particularly limited, and examples thereof include aliphatic polyols, polyols having an alicyclic structure, aromatic polyols, etc. In the present embodiment, from the viewpoint of flexibility of the water-absorbing anti-fogging layer, aliphatic polyols not having an alicyclic structure are preferred. Examples of carbonate esters include aliphatic carbonate esters such as dimethyl carbonate and diethyl carbonate, aromatic carbonate esters such as diphenyl carbonate, and cyclic carbonate esters such as ethylene carbonate. Among these, aliphatic carbonate esters are preferred from the viewpoint of availability and ease of production, and dimethyl carbonate is particularly preferred.

[0062] The polyether polyol can be used without any particular limitation so long as it is a compound having an ether bond (-O-) and two or more hydroxyl groups in one molecule. Specific examples of the compounds include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 3-methyl-1,5-pentanediol, 3,3-dimethylolheptane, diethylene glycol, dipropylene glycol, neopentyl glycol, cyclohexane-1,4-diol, cyclohexane-1,4-dimethanol, diol dimer acid, bisphenol A, bis(β-hydroxyethyl)benzene, xylylene glycol, glycerin, trimethylolpropane, and pentaerythritol. Examples of the polyether polyols include polyether polyols obtained by addition polymerization of alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide, etc., using as an initiator a compound having two or more, preferably 2 to 3, active hydrogen groups, such as low molecular weight polyols such as ethylene diamine, propylene diamine, toluene diamine, metaphenylene diamine, diphenylmethane diamine, xylylene diamine, etc.; and polyether polyols obtained by ring-opening polymerization of cyclic ether monomers such as alkyl glycidyl ethers such as methyl glycidyl ether, aryl glycidyl ethers such as phenyl glycidyl ether, and tetrahydrofuran.

[0063] In the present embodiment, the polyol compound may be a compound corresponding to two or more of polycaprolactone polyol, polycarbonate polyol, and polyether polyol. For example, the polyol compound may be a polyether polyester polyol having an ether bond and an ester bond. The polyol compound may contain two or more kinds of polycaprolactone polyol, polycarbonate polyol, and polyether polyol.

[0064] The hydroxyl value of the polyol compound is preferably 50 to 500 mgKOH / g, more preferably 100 to 350 mgKOH / g, and further preferably 150 to 250 mgKOH / g. By setting the amount of hydroxyl groups to an appropriate amount, the crosslinked structure caused by the reaction with the polyfunctional isocyanate compound described below is controlled, and the flexibility, elasticity, etc. of the water-absorbing anti-fogging layer can be further improved.

[0065] In the present embodiment, the mass average molecular weight (Mw) of the polyol compound is preferably 450 to 2,500, more preferably 500 to 1,500, and even more preferably 500 to 700. By selecting an appropriate molecular weight, it becomes easier to achieve a high compatibility between suppressing changes in the appearance of the water-absorbent anti-fogging layer due to improved flexibility and elasticity, and durability of the water-absorbent anti-fogging layer, such as gasoline resistance.

[0066] The content of the polyol compound in the anti-fog layer composition is preferably 5 to 200 parts by mass, more preferably 15 to 180 parts by mass, even more preferably 20 to 150 parts by mass, still more preferably 20 to 100 parts by mass, still more preferably 20 to 50 parts by mass, and even more preferably 20 to 40 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin. By setting the content within the above numerical range, it becomes easier to obtain the performance derived from the polyol compound, and it becomes easier to balance it with other components.

[0067] In the present embodiment, the polyol compound preferably contains a polycaprolactone polyol among the above-mentioned polycaprolactone polyols, polycarbonate polyols, and polyether polyols, and among the polycaprolactone polyols, it is particularly preferable to contain a polycaprolactone diol (a compound having a caprolactone structure and two hydroxyl groups). This is because the (meth)acrylic resin, which is component (A), has the structure of the above-mentioned general formula (2), i.e., a caprolactone structure, and therefore the polyol compound tends to have good compatibility with the (meth)acrylic resin, and tends to easily improve the anti-fogging performance without excessively increasing the crosslinking density.

[0068] [Component (C): Polyfunctional isocyanate compound] The water-absorbing anti-fogging layer composition preferably contains a polyfunctional isocyanate compound as component (C). When the anti-fogging layer composition contains a polyfunctional isocyanate compound, a crosslinking reaction occurs between the hydroxyl groups of the structural units (a-2) and (a-3) contained in the (meth)acrylic resin, which is component (A), and the hydroxyl groups of the polyol compound, which is component (B), and the polyfunctional isocyanate compound, resulting in a water-absorbing anti-fogging layer with excellent anti-fogging durability. The polyfunctional isocyanate compound is a compound having two or more isocyanate groups (including an isocyanate group protected by a leaving group) in one molecule. The number of functional groups in the polyfunctional isocyanate compound is preferably 2 to 6 per molecule, more preferably 2 to 4 per molecule.

[0069] Examples of polyfunctional isocyanate compounds include aliphatic diisocyanates such as lysine isocyanate, hexamethylene diisocyanate, and trimethylhexane diisocyanate; cyclic aliphatic diisocyanates such as hydrogenated xylylene diisocyanate, isophorone diisocyanate, methylcyclohexane-2,4-(or 2,6)-diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and 1,3-(isocyanatomethyl)cyclohexane; and tri- or higher functional isocyanates such as lysine triisocyanate.

[0070] The polyfunctional isocyanate compound of component (C) may be any of the above-mentioned compounds, or may be a polymer thereof such as a biuret type, an isocyanurate type, an adduct type, etc. Among these, a biuret type polyfunctional isocyanate compound having an appropriate rigidity is preferred.

[0071] In this embodiment, the content of the polyfunctional isocyanate compound in the water-absorbing anti-fogging layer composition is not particularly limited as long as it is blended according to the equivalent ratio (NCO) / (OH) described later. The content of the polyfunctional isocyanate compound in the anti-fogging layer composition is usually about 5 to 100 parts by mass, preferably 7 to 75 parts by mass, more preferably 10 to 60 parts by mass, even more preferably 10 to 50 parts by mass, still more preferably 15 to 40 parts by mass, and even more preferably 20 to 30 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin. It is considered that by setting the content within this numerical range, necessary and sufficient crosslinking is performed in the water-absorbing anti-fogging layer. The molar amount of the isocyanate groups (including blocked isocyanate groups) contained in the polyfunctional isocyanate compound relative to the hydroxyl groups of the (meth)acrylic resin and polyol compound (i.e., the equivalent ratio (NCO) / (OH)) is preferably in the range of 0.15 to 0.55. When the equivalent ratio (NCO) / (OH) is within the above range, the crosslinking density is sufficiently high, and as a result, the functions such as antifogging performance and solvent resistance as a water-absorbing antifogging layer are sufficient. From the viewpoint of functions such as antifogging performance and solvent resistance, the equivalent ratio (NCO) / (OH) is preferably 0.25 to 0.50, more preferably 0.35 to 0.45.

[0072] <Form of Water-Absorbing Anti-Fog Layer Composition> The water-absorbing anti-fogging layer composition may be of one-component type, that is, in a state in which all components other than the solvent are substantially uniformly mixed (dissolved or dispersed) in the solvent. When the polyfunctional isocyanate compound is a blocked isocyanate, the one-component type is preferred. In another embodiment, the water-absorbing anti-fogging layer composition may be a two-component type, which can improve the storage stability of the water-absorbing anti-fogging layer composition. For example, the water-absorbing anti-fogging layer composition may be composed of (1) liquid A containing a (meth)acrylic resin and / or a polyol compound and not containing a polyfunctional isocyanate compound, and (2) liquid B containing a polyfunctional isocyanate compound and not containing a (meth)acrylic resin or a polyol compound, and liquid A and liquid B may be stored in separate containers and mixed together immediately before use (application). In this case, components (additives, etc.) other than the (meth)acrylic resin, the polyol compound, and the polyfunctional isocyanate compound may be contained in liquid A or liquid B, or may be prepared in another container. In particular, when the polyfunctional isocyanate compound is not a blocked isocyanate (that is, when the isocyanate group is present in the system in the form of --NCO), the water-absorbing anti-fogging layer composition is preferably of the two-liquid type.

[0073] <Solvent> The coating liquid containing the water-absorbing anti-fogging layer composition may contain a solvent. The use of a solvent makes it easier to adjust the viscosity and solid content of the water-absorbing anti-fogging layer composition. Examples of the solvent include aromatic hydrocarbon solvents such as toluene and xylene; alcohol solvents such as methanol, ethanol, isopropyl alcohol, n-butanol, t-butanol, isobutanol, and diacetone alcohol; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester solvents such as ethyl acetate, propyl acetate, butyl acetate, and isobutyl acetate; and glycol ether solvents such as propylene glycol monomethyl acetate, propylene glycol monomethyl ether, and propylene glycol monomethyl ether acetate. Among these, t-butanol, diacetone alcohol, methyl ethyl ketone, ethyl acetate, and propylene glycol monomethyl ether acetate are preferred from the viewpoints of low reactivity with isocyanate, solubility, drying properties, and the like.

[0074] The content of the solvent in the coating solution is preferably 20 to 90% by mass, more preferably 30 to 85% by mass, and even more preferably 35 to 80% by mass, from the viewpoint of controlling the thickness of the water-absorbing anti-fogging layer.

[0075] <Other additives> The coating liquid may contain additives such as a curing catalyst, an ultraviolet absorber, a light stabilizer, a surfactant, a leveling agent, and an antifoaming agent, as necessary. When an additive is added to the coating liquid, the content of the additive is, for example, preferably 0.001 to 5 mass %, more preferably 0.01 to 4 mass %, and even more preferably 0.1 to 3 mass %, relative to the total mass of the anti-fog layer composition.

[0076] The coating liquid can be prepared by dissolving or dispersing the above-mentioned components, which are used as necessary, in a solvent. The components can be dissolved or dispersed in the solvent simultaneously or sequentially in any order. There is no particular limitation on the specific method for dissolving or dispersing the components, and any known method can be used without any limitation.

[0077] <Viscosity> From the viewpoint of enabling the formation of a uniform layer and obtaining a spectacle lens with more excellent anti-fogging performance, the viscosity of a coating solution containing the water-absorbing anti-fogging layer composition at 15°C is usually about 10 to 80 mPa·s, preferably 15 to 70 mPa·s, more preferably 20 to 65 mPa·s, even more preferably 20 to 50 mPa·s, and may be 25 to 45 mPa·s. When forming an anti-fogging layer by a dipping method using a coating liquid with high viscosity, liquid puddles are likely to occur, which may cause defects. However, in this embodiment, even if the viscosity of the coating liquid is high, it is possible to form a water-absorbent anti-fogging layer without causing liquid puddles. Therefore, the higher the viscosity of the coating liquid, the more pronounced the effect of the present disclosure tends to be. In the present disclosure, the viscosity is a viscosity measured in accordance with JIS Z 8803: 2011. Specifically, the viscosity is measured by the method described in the examples below.

[0078] <Solid content> The solid content of the coating solution containing the water-absorbing anti-fogging layer composition is preferably 10.0 to 40.0% by mass, from the viewpoint of facilitating the formation of a uniform layer and obtaining a spectacle lens having better anti-fogging performance. If it is 10.0% by mass or more, the water-absorbing anti-fogging layer can be made thicker. If it is 40.0% by mass or less, a water-absorbing anti-fogging layer of uniform thickness can be obtained. From the viewpoint of controlling the thickness of the water-absorbing anti-fogging layer and forming a uniform thickness, the solid content of the coating solution is more preferably 12.0 to 30.0% by mass, even more preferably 15.0 to 30.0% by mass, and even more preferably 16.5 to 24.5% by mass.

[0079] From the viewpoint of improving the anti-fogging performance, the total content of components (A), (B) and (C) in the solid content of the coating liquid is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and still more preferably 95% by mass or more, and is preferably 100% by mass or less, and may be substantially 100% by mass.

[0080] [Other layers] The manufacturing method for the eyeglass lens of this embodiment requires only that a water-absorbent anti-fogging layer is formed on at least one surface of the substrate, and other layers may or may not be formed on the one surface. Furthermore, in the manufacturing method for eyeglass lenses of this embodiment, a water-absorptive anti-fogging layer and / or other layers may be formed on the other surface of the substrate, or the water-absorptive anti-fogging layer and / or other layers may not be formed. The manufacturing method of the eyeglass lens of this embodiment may include a step of forming a functional layer other than the water-absorptive anti-fogging layer, from the viewpoint of imparting a function other than anti-fogging performance to the eyeglass lens.

[0081] Examples of the functional layer include an anti-fogging layer such as a hydrophilic anti-fogging layer, a hard coat layer, an anti-reflection layer, a primer layer, etc. As the functional layer, a known layer can be used. The functional layer may be formed by a spin coating method, or may be formed by, for example, an air spray method, an airless spray method, an electrostatic coating method, a roll coater method, a flow coater method, a dipping method, or the like.

[0082] The hydrophilic anti-fogging layer can be formed using, for example, surfactants such as anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants; organic polymer compounds such as polyethylene glycol and polyethylene glycol (meth)acrylate; and the like. The thickness of the hydrophilic anti-fogging layer is usually about 0.5 to 35 nm from the viewpoints of anti-fogging performance and ease of application. The hard coat layer can be formed, for example, using a resin composition containing a silicone resin. The resin composition may contain metal particles, colloidal silica, and the like. From the viewpoints of scratch resistance, durability, and the like, the thickness of the hard coat layer is usually about 0.5 to 5 μm. The antireflection layer has, for example, a structure in which low refractive index layers and high refractive index layers are alternately arranged. The antireflection layer usually has about 4 to 10 layers. The refractive index of the low refractive index layer is usually about 1.35 to 1.80 at a wavelength of 500 to 550 nm. The low refractive index layer is made of an inorganic oxide such as silicon oxide. The refractive index of the high refractive index layer is usually about 1.90 to 2.60 at a wavelength of 500 to 550 nm. The high refractive index layer is made of an inorganic oxide such as zirconium oxide, tantalum pentoxide, yttrium oxide, titanium oxide, niobium pentoxide, or aluminum oxide. The anti-reflection layer can be formed by vapor deposition. The primer layer can be formed using, for example, an acrylic resin, a melamine resin, a urethane resin, an epoxy resin, a polyvinyl acetal resin, an amino resin, a polyester resin, a polyamide resin, a vinyl alcohol resin, a styrene resin, a silicone resin, or a mixture or copolymer thereof.

[0083] For example, a water-absorptive anti-fogging layer can be formed on one surface and a functional layer on the other surface by a method for manufacturing a spectacle lens in which the following steps 1 to 3 are carried out in order. Step 1: A coating liquid containing an anti-fogging layer composition is applied to one surface of a substrate by spin coating to form a water-absorbing anti-fogging layer. Step 2: An anti-reflection layer is formed on the other surface of the substrate. Step 3: On the other side of the substrate having the antireflection layer obtained in step 2, a hydrophilic antifogging layer is formed.

[0084] Here, Fig. 1 is a cross-sectional schematic diagram of a spectacle lens manufactured according to one embodiment of the present disclosure. The spectacle lens manufactured by the manufacturing method including the above steps 1 to 3 is, for example, as shown in 1a of Fig. 1. [Water-absorbing anti-fog layer 32, base material 11, anti-reflection layer 22, hydrophilic anti-fog layer 23] The layers can be stacked in this order. In the above manufacturing method, it is preferable that one surface of the substrate is concave and the other surface of the substrate is convex. The convex surface that is likely to come into contact with external objects is configured with an antireflection layer and a hydrophilic antifogging layer, and the outermost layer of the concave surface that is unlikely to come into contact with external objects is configured with a water-absorbent antifogging layer, thereby making it possible to manufacture a spectacle lens that has antifogging performance and antireflection properties. In addition, by carrying out the above steps 1 to 3 in order, there is no risk of cracks occurring in the antireflection layer due to the baking temperature during the formation of the water-absorbent antifogging layer.

[0085] Another preferred embodiment is a method for producing a spectacle lens, which includes a step of forming a hard coat layer on at least the other surface of the substrate before carrying out the above step 1 or the above step 2. By using the above production method, it is possible to form a water-absorptive antifogging layer on one surface and a functional layer on the other surface. The spectacle lens produced by the production method including the above steps 1 to 3 and a step of forming a hard coat layer (HC) is, for example, as shown in FIG. 1 2a or FIG. 1 3a, [Water-absorbing anti-fog layer 32, base material 11, HC21, anti-reflection layer 22, hydrophilic anti-fog layer 23] [Water-absorbing anti-fog layer 32, HC31, base material 11, HC21, anti-reflection layer 22, hydrophilic anti-fog layer 23] The layers can be stacked in this order. In the above manufacturing method, it is preferable that one surface of the substrate is concave and the other surface of the substrate is convex. By configuring the convex surface that is likely to come into contact with external objects as an antireflection layer and a hydrophilic antifogging layer, and configuring the outermost layer of the concave surface that is unlikely to come into contact with external objects as a water-absorbent antifogging layer, it is possible to manufacture a spectacle lens that has antifogging performance, antireflection properties, and scratch resistance.

[0086] In another embodiment, a water-absorbent anti-fogging layer can be formed on one surface and a functional layer on the other surface by a manufacturing method for eyeglass lenses in which a hard coat layer is formed on at least the other surface of the substrate before or after carrying out the above-mentioned step 1, and a hydrophilic anti-fogging layer is formed on the above-mentioned hard coat layer on the other surface. Specifically, in the above-mentioned another embodiment, the following hard coat layer forming step, step 1, and step 3' are carried out. Hard coat layer forming step: before carrying out step 1, a hard coat layer is formed on at least the other surface of the substrate, or between step 1 and step 3', a hard coat layer is formed on the other surface of the substrate. Step 1: A coating liquid containing a water-absorbing anti-fogging layer composition is applied to one surface of a substrate by spin coating to form a water-absorbing anti-fogging layer. Step 3': A hydrophilic antifogging layer is formed on the hard coat layer on the other side obtained in the hard coat layer forming step.

[0087] Here, Fig. 2 is a cross-sectional schematic diagram of a spectacle lens manufactured according to one embodiment of the present disclosure. The spectacle lens manufactured by the manufacturing method including the above-mentioned hard coat layer forming step, step 1, and step 3', for example, as shown in Fig. 2 1b or Fig. 2 2b, [Water-absorbing anti-fog layer 32, base material 11, HC21, hydrophilic anti-fog layer 23] [Water-absorbing anti-fog layer 32, HC31, base material 11, HC21, hydrophilic anti-fog layer 23] The layers can be stacked in this order. In the above manufacturing method, it is preferable that one surface of the substrate is concave and the other surface of the substrate is convex. By configuring the convex surface, which is likely to come into contact with external objects, to have a hard coat layer and a hydrophilic anti-fogging layer, and configuring the outermost layer of the concave surface, which is unlikely to come into contact with external objects, to have a water-absorbent anti-fogging layer, it is possible to manufacture a spectacle lens that has anti-fogging performance and scratch resistance.

[0088] In the present disclosure, the examples, contents, and various physical properties of each of the above components may be arbitrarily combined with the items described as examples or preferred ranges in the detailed description of the invention. Furthermore, by adjusting the compositions described in the examples to those described in the detailed description of the invention, the disclosed embodiment invention can be practiced in the same manner as the examples over the entire range of the claimed composition. EXAMPLES

[0089] Next, the present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited to these examples in any way.

[0090] <Measurement evaluation> The coating solutions obtained in the following Production Examples and the eyeglass lenses obtained in the Examples were subjected to measurement and evaluation of the following items.

[0091] (Hydroxyl value) Measurements and calculations were performed according to the method specified in "7.1 Neutralization titration method" of JIS K 0070:1992 "Testing methods for acid value, saponification value, ester value, iodine value, hydroxyl value and unsaponifiable matter of chemical products." The acid value used to calculate the hydroxyl value was measured and calculated according to the method specified in "3.1 Neutralization titration method" of the above JIS standard.

[0092] (Number average molecular weight (Mn), mass average molecular weight (Mw), polydispersity (Mw / Mn)) The measurements were performed using gel permeation chromatography (GPC) under the following conditions: Equipment used: HLC8220GPC (manufactured by Tosoh Corporation) Columns used: TSKgel SuperHZM-M, TSKgel GMHXL-H, TSKgel G2500HXL, TSKgel G5000HXL (manufactured by Tosoh Corporation) Column temperature: 40℃ Standard material: TSKgel standard polystyrene A1000, A2500, A5000, F1, F2, F4, F10 (manufactured by Tosoh Corporation) Detector: RI (Differential Refraction) Detector Eluent: Tetrahydrofuran ·Flow rate: 1ml / min

[0093] (viscosity measurement) The measurements were performed at 15°C in accordance with JIS Z 8803:2011 using a vibration viscometer Viscomate VM-10A manufactured by Sekonic Corporation.

[0094] (Measurement of water-absorbent anti-fogging layer thickness) The thickness of the water-absorptive anti-fogging layer of the obtained eyeglass lens was measured using a non-contact film thickness measurement system FF8 manufactured by System Road Co., Ltd.

[0095] (Anti-fog performance) Under conditions of room temperature 25°C and humidity 40%, breath was blown onto the surface of the anti-fog layer of the obtained eyeglass lens for 10 seconds. The state of the anti-fog layer was visually observed from the start of the breath blowing to the end of the breath blowing, and was evaluated according to the following evaluation criteria. When anti-fog layers were formed on both sides of the eyeglass lens, each anti-fog layer was evaluated. A: No fogging observed at all (Excellent anti-fogging performance) B: Fog is observed and it takes more than 10 seconds for the fog to disappear (poor anti-fog performance)

[0096] (Puddle) The water-absorptive anti-fogging layer was visually observed for pooling and evaluated according to the following criteria. A: There is no significant change in the thickness of the layer from the center to the periphery, and the water-absorbing anti-fogging layer is formed with a uniform thickness. B: Liquid pools have formed around the edges

[0097] <Preparation of Coating Solution Containing Water-Absorbing Anti-Fog Layer Composition> [Production Example] (Synthesis of (meth)acrylic resin) A 500 ml flask equipped with a stirrer, a thermometer, a condenser, and a nitrogen gas inlet tube was charged with 150 parts by mass of propylene glycol monomethyl acetate (PGMAC) and heated to 110°C. Separately, 25 parts by mass of dimethylacrylamide (DMAA), 35 parts by mass of polycaprolactone-modified hydroxyethyl acrylate (manufactured by Daicel Corporation, Plaxel FA2D), 10 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 5 parts by mass of one-terminated methacrylate-modified polydimethylsiloxane (manufactured by JNC Corporation, Silaplane FM-0721, molecular weight 5000), 25 parts by mass of methyl methacrylate, and 1 part by mass of 1,1'-azobis(cyclohexane-1-carbonitrile) (manufactured by Wako Pure Chemical Industries, Ltd., V-40) were mixed. This mixed monomer was dropped into the 500 ml flask over a period of 2 hours with stirring, and reacted for 5 hours. Heating was stopped and the mixture was cooled to room temperature to obtain a resin solution containing a (meth)acrylic resin (solid content ratio: approximately 40% by mass). The hydroxyl value of the obtained (meth)acrylic resin was 57 mgKOH / g, the number average molecular weight (Mn) was 12,000, the mass average molecular weight (Mw) was 44,000, and the polydispersity (Mw / Mn) was 3.67. The glass transition temperature (Tg) of the (meth)acrylic resin calculated from the blending ratio of the monomers used based on the Fox formula was 32.8°C.

[0098] (Preparation of Coating Solution) The (meth)acrylic resin obtained above, polycaprolactone diol (manufactured by Daicel Corporation, Plaxel 205U, molecular weight 530, hydroxyl value 207 to 217 mgKOH / g), polyfunctional isocyanate compound (manufactured by Asahi Kasei Corporation, 24A-100, biuret type of hexamethylene diisocyanate, isocyanate group content 23.5 mass%, solid content 100 mass%), propylene glycol monomethyl ether acetate, diacetone alcohol, methyl ethyl ketone, t-butanol, and ethyl acetate were mixed to obtain a mixture. The contents of each component in the obtained mixture are as follows. (Meth)acrylic resin: 14.7% by mass Polycaprolactone diol: 4.4% by mass Polyfunctional isocyanate compound: 3.4% by mass Propylene glycol monomethyl ether acetate: 28.5% by mass Diacetone alcohol: 18.5% by mass Methyl ethyl ketone: 13.5% by mass t-Butanol: 8.5% by mass Ethyl acetate: 8.5% by weight Then, ethyl acetate, methyl ethyl ketone, and diacetone alcohol were added to the above mixture and mixed to adjust the viscosity to 35.8 mPa·s and the solid content to 21.7 mass%, thereby obtaining a coating liquid containing a water-absorbing anti-fogging layer composition. When 100 parts by mass of the (meth)acrylic resin and 30 parts by mass of the polyol compound (polycaprolactone diol) were uniformly mixed, the measured hydroxyl value of the mixture was 93 mgKOH / g.

[0099] <Manufacture of eyeglass lenses> [Example 1] The substrate used was a thiourethane plastic lens "EYNOA" (manufactured by HOYA Corporation, refractive index 1.67). The coating liquid obtained in the above manufacturing example was applied by spin coating to the convex or concave surface of a substrate under the conditions shown in Table 1. After the above coating, the substrate was pre-baked at a temperature of 100° C. for 20 minutes, and then baked at a temperature of 120° C. for 120 minutes to produce a spectacle lens having a single anti-fogging layer on the substrate. The thickness of the water-absorptive anti-fogging layer, anti-fogging performance, and liquid pooling evaluation results of the obtained spectacle lens are shown in Table 1.

[0100] [Examples 2 to 5] A spectacle lens was produced in the same manner as in Example 1, except that the coating liquid was applied onto the substrate under the conditions shown in Table 1.

[0101] [Table 1]

[0102] [Example 6] (Preparation of Hard Coat Composition) 17 parts by mass of γ-glycidoxypropyltrimethoxysilane, 30 parts by mass of methanol, and 28 parts by mass of water-dispersed colloidal silica (solid content 40% by mass, average particle size 15 μm) were added to a glass container equipped with a magnetic stirrer, mixed thoroughly, and stirred for 24 hours at a flow temperature of 5° C. Next, 15 parts by mass of propylene glycol monomethyl ether, 0.05 parts by mass of a silicone surfactant, and 1.5 parts by mass of aluminum acetylacetonate as a curing agent were added, stirred thoroughly, and then filtered to prepare a hard coat composition.

[0103] (Manufacture of eyeglass lenses) The substrate used was a thiourethane plastic lens "EYNOA" (manufactured by HOYA Corporation, refractive index 1.67). (1) The hard coat composition was applied to a substrate by dipping (pulling speed 30 cm / min) and heated at 90°C for 120 minutes to form hard coat layers on both sides of the substrate. The thickness of the hard coat layer on the convex side was 3.06 μm at the center of the lens substrate. The thickness of the hard coat layer on the concave side was 2.86 μm at the center of the lens substrate. (2) Next, the coating solution obtained in the above-mentioned manufacturing example was applied by spin coating onto the above-mentioned hard coat layer on the concave side of the substrate. After the above-mentioned coating, the substrate was pre-baked at 100°C for 20 minutes, and then baked at 120°C for 120 minutes to form a water-absorbing anti-fogging layer. The conditions of the spin coating method, the thickness of the water-absorbing anti-fogging layer, and the evaluation results of the liquid pooling are shown in Table 2. (3) Next, on the hard coat layer on the convex side of the substrate, a 500 nm thick antireflection layer (the uppermost layer is a silicon oxide layer) was formed by vacuum deposition. Specifically, a silicon oxide layer was formed as a first underlayer (low refractive index layer) by vacuum deposition on the hard coat layer formed on the convex side of the substrate, and zirconium oxide layers and silicon oxide layers were alternately laminated as the second to seventh layers to form an antireflection layer such that the uppermost layer was a silicon oxide layer. (4) Next, the coating solution for the hydrophilic anti-fog layer was applied onto the anti-reflection layer on the convex side of the substrate by spin coating, and then baked at 60° C. for 120 minutes to form a hydrophilic anti-fog layer with a thickness of 20 nm. The coating solution for the hydrophilic anti-fogging layer was prepared by dissolving 5 g of sodium polyoxyethylene lauryl ether sulfate (anionic surfactant, Nikkol SBL-4N manufactured by Nikko Chemicals Co., Ltd.) in 95 g of water.

[0104] In Example 6, the layer structure of the obtained eyeglass lens was as shown in FIG. 1, 3a, from the concave side. [Water-absorbing anti-fogging layer 32, HC 31, substrate 11, HC 21, anti-reflection layer 22, hydrophilic anti-fogging layer 23] (3a in FIG. 1) It is. The anti-fogging performance of the obtained eyeglass lens was evaluated as "A" for both the concave and convex surfaces.

[0105] [Table 2]

[0106] [Example 7] (Manufacture of eyeglass lenses) The substrate used was a thiourethane plastic lens "EYNOA" (manufactured by HOYA Corporation, refractive index 1.67). (1) The hard coat composition prepared in Example 6 was applied to the convex side of the substrate by spin coating. After the application, the substrate was heated at 90° C. for 120 minutes to form a hard coat layer having a thickness of 3 μm on the convex surface of the substrate. (2) Next, the coating solution obtained in the above manufacturing example was applied to the concave side of the substrate by spin coating. After the above coating, the substrate was pre-baked at 100°C for 20 minutes, and then baked at 120°C for 120 minutes to form a water-absorbing anti-fogging layer. The conditions of the spin coating method, the thickness of the water-absorbing anti-fogging layer, and the evaluation results of the liquid pooling are shown in Table 3. (3) Next, in the same manner as in Example 6, an antireflection layer (the uppermost layer was a silicon oxide layer) having a thickness of 500 nm was formed on the hard coat layer on the convex side of the substrate by vacuum deposition. (4) Next, in the same manner as in Example 6, a hydrophilic antifogging layer having a thickness of 20 nm was formed on the antireflection layer on the convex surface side of the substrate.

[0107] In Example 7, the layer structure of the obtained eyeglass lens was as shown in FIG. 1A, from the concave side, [Water-absorbing anti-fog layer 32, base material 11, HC21, anti-reflection layer 22, hydrophilic anti-fog layer 23] It is. The anti-fogging performance of the obtained eyeglass lens was evaluated as "A" for both the concave and convex surfaces.

[0108] [Table 3]

[0109] [Examples 8 to 15] A spectacle lens was produced in the same manner as in Example 1, except that the coating liquid was applied onto the substrate under the conditions shown in Table 4.

[0110] [Table 4]

[0111] [Reference example] The substrate used was a thiourethane plastic lens "EYNOA" (manufactured by HOYA Corporation, refractive index 1.67). (1) The coating solution obtained in the above-mentioned manufacturing example was applied to the substrate by dipping. After the above-mentioned coating, the substrate was pre-baked at 100°C for 20 minutes, and then post-baked at 120°C for 120 minutes to form a water-absorbing anti-fogging layer having a thickness of 12.7 μm on both sides of the substrate. (2) Next, in the same manner as in Example 6, a 500 nmμm-thick antireflection layer (the uppermost layer was a silicon oxide layer) was formed by vacuum deposition on the water-absorbing antifogging layer on the convex side of the substrate. (3) Next, in the same manner as in Example 6, a hydrophilic antifogging layer having a thickness of 20 nm was formed on the antireflection layer on the convex surface side of the substrate.

[0112] Here, FIG. 3 is a schematic cross-sectional view of a spectacle lens for reference. In the reference example, the layer structure of the obtained eyeglass lens is as shown in FIG. 3 1c, from the concave side: [Water-absorbing anti-fog layer 32, base material 11, water-absorbing anti-fog layer 24, anti-reflection layer 22, hydrophilic anti-fog layer 23] It is. In the eyeglass lens obtained in the Reference Example, an anti-fogging layer was formed on the outermost layers of the concave and convex surfaces with a few steps. However, because the anti-reflection layer was formed on a relatively soft water-absorbent anti-fogging layer, the anti-reflection layer became wrinkled, and the eyeglass lens was not provided with the desired function. The manufacturing method of the spectacle lens of this embodiment can form the same or different anti-fogging layers on both sides of the substrate, so that it is possible to manufacture a spectacle lens having a water-absorbent anti-fogging layer on one side and no water-absorbent anti-fogging layer on the other side. Therefore, this embodiment can manufacture a spectacle lens having a water-absorbent anti-fogging layer on only one side without forming an anti-reflection layer on the water-absorbent anti-fogging layer as in the above-mentioned Reference Example, so that it is possible to easily realize a desired layer structure and to impart a desired function to the spectacle lens.

[0113] Finally, the embodiments of the present disclosure will be summarized. In a method for producing a spectacle lens according to an embodiment of the present disclosure, a coating liquid containing a water-absorbent anti-fogging layer composition is applied to at least one surface of a substrate by spin coating to form a water-absorbent anti-fogging layer. According to the above-described embodiment, it is possible to provide a method for manufacturing a spectacle lens, which is capable of forming the same or different anti-fogging layers on both sides of a substrate with almost no liquid pooling.

[0114] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present disclosure is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. In the present disclosure, the examples, contents, and various physical properties of each of the above components may be arbitrarily combined with the items described as examples or preferred ranges in the detailed description of the invention. Furthermore, by adjusting the compositions described in the examples to those described in the detailed description of the invention, the disclosed embodiments can be practiced in the same manner as the examples over the entire range of the claimed compositions. [Explanation of symbols]

[0115] 1a, 2a, 3a, 1b, 2b, 1c: Eyeglass lenses 11: Base material 21, 31: Hard coat layer 22: Anti-reflection layer 23: Hydrophilic anti-fog layer 24, 32: Water-absorbing anti-fog layer

Claims

1. A method for producing a spectacle lens, comprising applying a coating liquid containing a water-absorbent anti-fogging layer composition to at least one surface of a substrate by a spin coating method to form a water-absorbent anti-fogging layer, the water-absorbing anti-fogging layer composition contains a constitutional unit derived from acrylamide, The coating liquid has a viscosity of 10 to 80 mPa·s and a solid content of 10.0 to 40.0 mass %, The coating by the spin coating method includes a first-stage coating in which spin coating is performed under conditions of a rotation speed of 200 to 600 rpm and a holding time of 1 to 10 seconds, and a second-stage coating in which spin coating is performed under conditions of a rotation speed of 700 to 1500 rpm and a holding time of 1 to 10 seconds.

2. The method for manufacturing a spectacle lens according to claim 1 , further comprising forming an anti-fogging layer on the other surface of the substrate by a spin coating method.

3. The method for manufacturing a spectacle lens according to claim 2 , wherein a thickness of the water-absorptive anti-fogging layer on said one surface and a thickness of the anti-fogging layer on said other surface are the same or different.

4. The method for manufacturing a spectacle lens according to claim 2 or 3, wherein the anti-fogging layer on the other surface is a water-absorbent anti-fogging layer or a hydrophilic anti-fogging layer.

5. The method for manufacturing a spectacle lens according to any one of claims 1 to 4, wherein a coating liquid containing the water-absorbing anti-fogging layer composition is applied to the other surface of the substrate by a spin coating method to form a water-absorbing anti-fogging layer.

6. The method for manufacturing a spectacle lens according to any one of claims 1 to 5, wherein the water-absorbing antifogging layer is formed directly on at least one surface of the substrate.

7. The method for producing a spectacle lens according to any one of claims 1 to 4, comprising carrying out the following steps 1 to 3 in order: Step 1: A coating liquid containing the water-absorbing anti-fogging layer composition is applied to one surface of the substrate by spin coating to form a water-absorbing anti-fogging layer. Step 2: An anti-reflection layer is formed on the other surface of the substrate. Step 3: On the other side of the substrate having the antireflection layer obtained in step 2, a hydrophilic antifogging layer is formed.

8. The method for manufacturing a spectacle lens according to claim 7 , further comprising forming a hard coat layer on at least the other surface of the substrate before carrying out the step 1 or the step 2.

9. The method for manufacturing a spectacle lens according to any one of claims 1 to 8, wherein one surface of the substrate is a concave surface and the other surface of the substrate is a convex surface.

10. The method for manufacturing a spectacle lens according to any one of claims 1 to 9, wherein the water-absorbing antifogging layer on at least said one surface is an outermost layer.

11. The method for manufacturing a spectacle lens according to any one of claims 1 to 10, wherein the water-absorbing antifogging layer on at least said one surface is a single layer.

12. The method for producing a spectacle lens according to any one of claims 1 to 11, wherein the water-absorbing anti-fogging layer composition comprises the following components (A) to (C): Component (A): A (meth)acrylic resin (A) having a structural unit derived from a monomer (a-1) represented by the following general formula (1), a structural unit derived from a monomer (a-2) represented by the following general formula (2), a structural unit derived from a hydroxyalkyl (meth)acrylate (a-3), and a structural unit derived from a monomer (a-4) represented by the following general formula (3): Component (B): Polyol compound (B) Component (C): Polyfunctional isocyanate compound (C) 【Chemistry 1】 [In general formula (1), R 1 is a hydrogen atom or a methyl group, R 2 and R 3 are each independently a hydrogen atom or a linear or branched alkyl group having 1 to 3 carbon atoms; R 2 and R 3 may be the same or different. 【Chemistry 2】 [In general formula (2), R 4 is a hydrogen atom or a methyl group, and m is an integer of 1 to 5. 【Chemistry 3】 [In general formula (3), R 5 is a hydrogen atom or a methyl group, R 6 is a divalent organic group, and n is 0 or an integer of 1 or more.

Citation Information

Patent Citations

  • JP1976137342U

  • Antifogging optical article and its production

    JP2000075104A

  • Anticlouding optical component

    JP2004323794A

  • Antifogging spectacle lens and its manufacturing method

    JP2005234066A

  • Coating composition, cured film, and article having the cured film

    JP2019094468A